100 Jahre Hauptgebäude der Universität Hamburg. Reden der Festveranstaltung am 13. Mai 2011 und anlässlich der Benennung der Hörsäle H und K im Hauptgebäude der Universität nach dem Sozialökonomen Eduard Heimann (1889-1967) und dem Juristen Albrecht Mendelssohn Bartholdy (1874-1936) - Der Präsident der Universität Hamburg (Hamburger Universitätsreden Neue Folge, 2012)
On the occasion of the 100th anniversary of the University of Hamburg's main building, a ceremony was held on May 13th, 2011. The keynote speaker was Heinz-Elmar Tenorth, Professor of Historical Education in Berlin. Heinz Rieter and Rainer Nicolaysen awarded two lecture hall names, the socio-economic economist Eduard Heimann (1889-1967)(Lecture Hall H) and the lawyer Albrecht Mendelssohn Bartholdy (1874-1936) (Lecture Hall K). Thus, the programme for naming the seven lecture halls of the University's main building after outstanding scientists who were expelled from the Nazi regime came to an end.Detailed information on all names of the lecture hall can be found in the anthology The main building of the University of Hamburg as a place of remembrance, which was published on the occasion of the anniversary.